The impact of psychoeducational group with self-instruction techniques toward career decision making, self-esteem, and self-efficacy - Meitasari, Meitasari; Maba, Aprezo Pardodi; Rahmawati, Ari; Basith, Abd. (Konselor, 2020)
One of the development tasks of adolescence is preparing career choices. Various methods have been carried out by authors in order to create an appropriate method to help adolescents. The purpose of the study was to examine the psychoeducational groups with self-instruction techniques in improving career decision-making skills, self-esteem, and self-efficacy. This preliminary study consisted of 60 participant who have low level of self-esteem, self-efficacy and career decision making. The instrument used to obtain data is the psychological scale of career decision making, self-esteem, and self-efficacy, all of which have been tested for validity and reliability. The data findings were analyzed by MANOVA and t-test. The results show that career decision making (F = 52.28, p <0.05), self-esteem (F = 28.10, p <0.05), and self-efficacy (F = 34.70, p <0.05) can be improved using psychoeducational groups with self-instruction techniques. The implications for the practice of guidance and counseling will be discussed. Thus psychoeducational groups with self-instruction techniques can be increased self-esteem, self-efficacy and career decision making.